Tinjauan Maqashid Syariah terhadap Kawin Paksa - Karenina Nurissa Karen; Yandi Maryandi; Ilham Mujahid (UNISBA Press, 2022)
Abstract. Marriage according to Islamic law is marriage, which is a very strong contract miitsaqan ghaliizhan to obey Allah commands and is a form of worship. At this time forced marriages are commonplace, forced marriages are marriages not of their own will in their own decisions but under the compulsion of their guardians or other people without their willingness. Cases like this were found in the village of North Cikareo, which were committed by parents against their daughters. Maqasyid sharia are the goals that Islamic law wants to realize as the reason it was revealed for the benefit of the servants of Allah. Researchers in their research formulate the formulation of the problem as follows: How is the Maqashid Sharia Review on forced marriages; How does forced marriage affect spouses and parents; The purpose of this research is to answer the problem formulation. This research is a field research, using qualitative descriptive analysis. The results of his research that forced marriages in North Cikareo Village are in accordance with the pillars and conditions of marriage and are included in the level of daruriyat benefit because they can maintain religion, soul, property, intellect and offspring; The forced marriage carried out in North Cikareo Village brought many positive impacts for himself, his family, and the environment. Abstrak. Perkawinan menurut hukum Islam adalah pernikahan, yaitu akad yang sangat kuat miitsaqan ghaliizhan untuk mentaati perintah Allah SWT dan merupakan suatu bentuk ibadah. Pada saat ini perkawinan secara paksa lumrah terjadi, perkawinan paksa merupakan suatu pernikahan bukan kehendak sendiri dalam keputusannya sendiri melainkan atas keterpaksaan dari wali ataupun orang lain tanpa adanya kerelaan dalam dirinya. Kasus seperti ini dijumpai di Desa Cikareo Utara yang dilakukan oleh orang tua terhadap anak perempuannya. Maqasyid syariah merupakan tujuan-tujuan yang ingin diwujudkan oleh syariat islam sebagai alasan diturunkannya demi kemaslahatan hamba-hamba Allah. Peneliti dalam penelitiannya merumuskan rumusan masalah sebagai berikut: Bagaimana Tinjauan Maqashid Syariah terhadap kawin paksa; Bagaimana Dampak perkawinan paksa terhadap pasangan dan orang tua; adapun tujuan dari penelitian ini yaitu untuk menjawab rumusan masalah. Penelitian ini merupakan penelitian lapangan, menggunakan analisis deskriptif kualitatif. Hasil penelitiannya bahwa pernikahan paksa di Desa Cikareo Utara sesuai dengan rukun dan syarat perkawinan dan termasuk kedalam tingkatan kemaslahatan daruriyat karena dapat memelihara agama,jiwa,harta,akal dan keturunan; nikah paksa yang dilakukan di Desa Cikareo Utara ini banyak membawa dampak positif bagi dirinya sendiri, keluarga, serta lingkungan.